(untitled) (Global Business Management Review (GBMR), 2022)
Dr. Dileep Kumar M, is a Professor of OYA-GSB, Universit Utara Malaysia, having wide experience in teaching, writing, research, consultancy and training. He has worked at many prestigious institutes abroad. With a Doctorate in Organisational Behavior, he has written many short case studies in the area of OB/HR and Management. He has several international and national peer reviewed journal publications and online publications. He presented several papers in international and national conferences and the papers are published in the conference proceedings. Dr. Dileep Kumar is a nationally and internationally recognized expert in case study writing in business management and author of six books. He has published many books and monographs like, Glue of Organizational Culture, Impact of Organisational Culture Upon Employees and Employers Behavior, Case Studies in Organisational Behavior Human Resource Management and Management, Stress and Coping Strategies, Innovative Ways to Combat Job Stress etc. He is the editor and editorial member of many national and international journals. This book titled, 50 Short Case Studies in Business Management”, is his maiden literary endeavor, soon after join our graduate school.